SISTEM PAKAR UNTUK MENDIAGNOSIS HAMA PENYAKIT TANAMAN SEMANGKA MENGGUNAKAN METODE CERTAINTY FACTOR DAN METODE BAYES - Luqman Imam; Henki Bayu Seta; Ria Astriratma (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
Watermelon is one of the most popular fruits by the general public. Apart from the benefits of watermelon, watermelon also has several diseases that are difficult for farmers to know, such as fruit rot (anthracnose), fruit scabies (bacterial fruit blotch), and others. Although watermelon disease is common, there are still many farmers who do not know about this problem. Therefore, an expert system for watermelon disease detection can be used using the certainty factor algorithm and the Bayes method. Based on the problems that occurred, this study raised the title